A Review in E-Government Service Quality Measurement - Wael Jabbar Abed Al-Nidawi; Saba Kamil Jaafar Al-Wassiti; Mahdi Athab Maan; Marini Othman (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Governments are responsible for providing services to the public easily, efficiently, therefore they introduced electronic government as a way to minimize costs, enhance services, save time and augment performance and efficacy in the public sector. E-service Quality is one of the critical issues in the failure or success of e-government projects. It promotes the efficiency and effectiveness of governments and the relationships with users and enhances their satisfactions. Measurement of e-service quality is a complex process because it depends on citizens’ perception that is difficult to be realized and measured. This paper aims to review scales measurement of e- government services quality that providing an evaluating scale based on defining the significant e- service quality dimensions. These dimensions cover important e-services requirements to enhance e-service quality.